A CASE SERIES ON THE MANAGEMENT OF INTUSSUSCEPTION IN INFANTS: CHALLENGING ENTITY WHILE DEPLOYED IN REMOTE SETTINGS DURING OVERSEAS DEPLOYMENT - KULKARNI, PRANAV CHANDRAKANT; VERMA, VISHAL; HIREMATH, RAVISHEKAR N; KAMEWAD, AMIT; M, KALE; YADAV, NARENDER; RAJ, RISHI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Intussusception is a major cause of acute intestinal obstruction in children. Idiopathic intussusception occurs predominantly under the age of 3 and is rare after the age of 6 years. This paper reports three cases of infant intussusception, including one Ileo-ceaco-colic intussusception in an 8-month-old baby boy (an uncommon condition in small infants) treated at the peripheral hospital during deployment in remote settings. This case series highlights diverse signs and symptoms of intussusception, and very few cases present with a typical triad of intussusception (abdominal pain, vomiting, and red currant jelly stool). Strong clinical suspicion is required for the diagnosis of intussusception, especially in a remote peripheral setting where diagnostic facilities are scarce. Furthermore, the surgeon should be ready for a surprise challenge after opening Pandora’s box. Delay in diagnosis may result in complications such as perforation, necrosis, and death. An important lesson learned from these three different cases is that the postoperative behavior of surgically reduced intussusception differs from case by case, and we have to be careful and alert during the postoperative period.